Estimating the diagnostic accuracy of rheumatoid factor in UK primary care: a study using the clinical practice research datalink - Miller, A; Nightingale, A; Sammon, C; Mahtani, K; Holt, T; McHugh, N; Luqmani, R (Oxford University Press, 2015)
Objective: To investigate the diagnostic accuracy of RF as a test for RA in primary care and its impact on referral times using the Clinical Practice Research Datalink. Methods: We identified all patients with a first RF test recorded in the Clinical Practice Research Datalink between 1 January 2000 and 31 December 2008 and those diagnosed with RA within 2 years of testing. We calculated likelihood ratios (LRs), sensitivity, specificity and predictive values of RF for a diagnosis of RA. We compared time to hospital referral in those testing positive and negative using Kaplan–Meier failure curves and log-rank tests. Results: Of 62 436 first RF tests, 4679 (7.5%) were positive. There were 1753 incident cases of RA, of which 57.8% were seropositive. The positive LR for RF was 9.5 (95% CI 9.0, 10.0) and the negative LR was 0.5 (95% CI 0.4, 0.5). Sensitivity and specificity were 57.8% (95% CI 55.4%, 60.1%) and 93.9% (95% CI 93.7%, 94.1%) and the positive predictive value and negative predictive value were 21.4% (95% CI 20.3%, 22.6%) and 98.7% (95% CI 98.6%, 98.8%), respectively. Median time to first hospital contact after the first RF test in those with seropositive vs seronegative results was 54 days (95% CI 49, 58) vs 150 (95% CI 147, 152). Conclusion: Only 2.8% of patients undergoing RF testing were diagnosed with RA, suggesting that RF is used to screen patients with musculoskeletal symptoms rather than those with more specific features of RA. A positive RF test may be helpful in diagnosing RA in primary care but performs badly in excluding RA and may delay referral.